2015
DOI: 10.1159/000368293
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic H<sub>3</sub>-Heteroreceptors as a Potential Mediator of Betahistine-Induced Increase in Cochlear Blood Flow

Abstract: Objective: Betahistine is a histamine-like drug that is considered beneficial in Ménière's disease by increasing cochlear blood flow. Acting as an agonist at the histamine H1-receptor and as an inverse agonist at the H3-receptor, these receptors as well as the adrenergic α2-receptor were investigated for betahistine effects on cochlear blood flow. Materials and Methods: A total of 54 Dunkin-Hartley guinea pigs were randomly assigned to one of nine groups treated with a selection of H1-, H3- or α2-selective ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…We demonstrated that topical application of FTY-720 is able to reverse the effects of TNF on cochlear blood flow: application of FTY-720 caused a significant increase in cochlear blood flow. The fact that the cochlear blood flow had also decreased somewhat in the group that had received a placebo twice could be explained by increased clotting in the capillaries caused by the surgical manipulation, a phenomenon that has previously been reported in this animal model (20). Even though this could be a potential confounder in the animal model used in this study, this also raises the threshold levels to obtain significant results, assuming that FTY-720 would increase cochlear blood flow compared with previous values.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We demonstrated that topical application of FTY-720 is able to reverse the effects of TNF on cochlear blood flow: application of FTY-720 caused a significant increase in cochlear blood flow. The fact that the cochlear blood flow had also decreased somewhat in the group that had received a placebo twice could be explained by increased clotting in the capillaries caused by the surgical manipulation, a phenomenon that has previously been reported in this animal model (20). Even though this could be a potential confounder in the animal model used in this study, this also raises the threshold levels to obtain significant results, assuming that FTY-720 would increase cochlear blood flow compared with previous values.…”
Section: Discussionsupporting
confidence: 62%
“…The technique applied in this experiment has been previously described (19)(20)(21). After induction of anesthesia, a cervical venous catheter was surgically implemented.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Functionally, the acute effect might be related to an action on the vascular tree as seen in experimental models by the betahistine-induced increase in cochlear and vestibular blood flow ( 28 ). This mechanism of action has been attributed to a direct action on the histamine H3 heteroreceptors located in the cochlear vascular network ( 30 ), and it is supposed to be responsible for the reduction in the number of vertigo attacks in Menière's disease patients. Ihler et al ( 28 ) showed that betahistine exerts a dose dependent effect on cochlear stria vascularis blood flow in guinea pig in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the histamine H 3 autoreceptors releases histamine that could rebalance the VN cells activity on both sides by actions at the post-synaptic histamine H 1 ( 51 ) or H 2 ( 52 54 ) receptors. In addition to this specific mechanism of action, betahistine could improve the microcirculation of the inner ear as well as homeostasis of endolymphatic fluid by acting on H3 and H1 receptors ( 30 , 31 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Betahistine is a strong H3 antagonist and a weak H1 agonist26 with three sites of action. Firstly, it increases dose-dependent cochlear blood flow,27 mainly via the H3 receptor as an inverse agonist 28. Because betahistine has a strong first pass effect and is metabolised in the liver into three metabolites, not only betahistine but also its major metabolite aminoethylpyridine increases cochlear blood flow 29.…”
Section: Introductionmentioning
confidence: 99%